Environmental Effects of Public Transport: On the Gap between Average and Marginal Costs - Piet Rietveld (Tinbergen Institute, 2001)
Given the difference between peak and off-peak occupancy rates in public transport, the average emission pertraveller kilometre is lower in the peak than during the off-peak period. For cars a reverse pattern can be observed.However, in this paper it is argued that it is much more fruitful to analyse environmental effects in marginal than inaverage terms. This calls for a careful analysis of capacity management policies of public transport suppliers thatare facing increases in demand both during the peak and off-peak period. A detailed analysis of capacitymanagement of the Netherlands Railways reveals that the off-peak capacity supply is mainly dictated by thedemand levels during the peak period. Issues that receive attention in the analysis are the effects of frequencyincreases and size of vehicle increases on environmental effects. Also environmental economies of vehicle size aretaken into account in the analysis. The main conclusion is that the marginal environmental burden during the peakis much higher than is usually thought, whereas it is almost zero at the off-peak period. Thus, one arrives at apattern that is entirely reversed compared with the average environmental burden. The conclusion is that policiesbased on average environmental performances would lead to misleading conclusions.
Keywords: 330; railways; service frequency; vehicle size; occupancy rate; Umweltbelastung; Theorie; Schienenverkehr